Kebenaran Ilmiah dalam Perkembangan Ilmu Pengetahuan - Farida, Nur; Magistra Pangestuti, Shallya; Prihatini , Yenny; Ketut Mahardika , I (Universitas Insan Budi Utomo, 2024)
: Philosophy of science is a philosophical reflection that never knows a stopping point in exploring scientific areas to reach truth or reality, something that will never be finished thinking about and will never be finished explaining. Philosophy of science can be a critical dialogue partner for the development of science because it is considered to be a medium between various branches of science so they can interact with each other. This research aims to examine scientific truth in the development of science. The method used in this research is literature study. Based on the results of the literature review, it is known that scientific truth cannot be separated from science or scientific knowledge because science or scientific knowledge is the actualization of scientific truth. Theories of truth can be used to find out whether a statement or hypothesis is the truth or not, including coherence theory, correspondence theory, and pragmatic theory. Scientific truth can be used to prove pre-existing theories through the application of the scientific method. These scientific method steps can be applied in the field of education to prove existing theories and concepts. Thus, science is dynamic. What was considered right yesterday may not be considered right today, and what is considered right today is not a fixed price for declaring it wrong tomorrow. The results of the research can provide insight into the implementation of scientific truths in the development of science and its application in the field of education, especially in the learning process.